2003
DOI: 10.1161/01.hyp.0000047104.42047.9b
|View full text |Cite
|
Sign up to set email alerts
|

Antisense to Epidermal Growth Factor Receptor Prevents the Development of Left Ventricular Hypertrophy

Abstract: Abstract-We previously demonstrated that left ventricular hypertrophy (LVH) induced by angiotensin II infusion requires epidermal growth factor receptor (EGFR) activation to mediate the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) pathway. To test whether the EGFR-mediated MAPK/ERK activation plays an important role in development and maintenance of LVH in spontaneously hypertensive rats (SHR), we investigated the effects of antisense oligodeoxynucleotide to EGFR (EGFR-AS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 35 publications
0
45
0
1
Order By: Relevance
“…Therefore, these truncated variants represent a tool to differentiate the consequences of nongenomic and genomic signaling and may help us to learn more about the pathophysiological relevance of nongenomic signaling. It has been shown that the EGFR-ERK1/2 signaling pathway plays a central role in cardiovascular fibrosis (53,54). Thus, the activation of this pathway by nongenomic MR signaling could contribute to its pathophysiological effects on cardiovascular tissue (4).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these truncated variants represent a tool to differentiate the consequences of nongenomic and genomic signaling and may help us to learn more about the pathophysiological relevance of nongenomic signaling. It has been shown that the EGFR-ERK1/2 signaling pathway plays a central role in cardiovascular fibrosis (53,54). Thus, the activation of this pathway by nongenomic MR signaling could contribute to its pathophysiological effects on cardiovascular tissue (4).…”
Section: Discussionmentioning
confidence: 99%
“…Further, EGF acts as a potent vasoconstrictor of arteries (Florian and Watts, 1999), and increased EGFR expression was found in the hypertrophied left ventricle (LV) of spontaneous hypertensive rats (Fujino et al, 1998). Also, receptor tyrosine kinase inhibitors, such as EGFR tyrosine kinase inhibitor 4-(39-chloroanilino)-6,7-dimethoxyquinazoline (AG1478), and EGFR antisense oligonucleotides attenuate vasoconstriction and elevation of blood pressure in Ang II-induced hypertension (Kagiyama et al, 2002(Kagiyama et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…15,23,24 The importance of EGFR in mediating pathophysiological effects of heterologous signaling systems is supported by its role in endothelin-induced fibrogenic effects. 15 Endothelin-induced phosphorylation of the mitogen-activated protein kinase and endothelin-induced increase in collagen I gene activity were completely prevented by an inhibitor of the EGFR kinase.…”
mentioning
confidence: 99%